The Determinant of Micro, Small, and Medium Tax Revenue on Tax Office Performance Moderated the Tax Target - Sofianti, Evin; Indupurnahayu; Aminda, Renea Shinta; Lysandra, Shanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the factors that affect the performance of tax office and micro small medium enterprises (MSME) tax revenue. The research method used is quantitative. The data is collected by distributing questionnaires to 100 micro small medium enterprises (MSME). Data was processed by using Structural Equalling Modeling (SEM) and hypothesis testing using the SmartPLS (Partial Least Square) method. The results of the study on the determinants of tax revenue consisting of policies, socialization, the number of tax returns, turnover, and WP compliance in the implementation of tax obligations have a significant effect on micro small medium enterprises (MSME) tax revenue in Bogor Regency. The study also found that socialization of policies and regulations for MSME needs to be improved in order to optimize tax office performance and tax revenue. In addition, the number of registered taxpayers is not balanced with the total number of MSME, moreover the taxpayer of MSME is dominated by the micro scale. Implications for tax office performance that cause socialization and to micro small medium enterprises (MSME) are not optimal. By understanding tax policies and regulations for MSMEs it is hoped that compliance and awareness of MSME taxpayers in fulfilling their tax obligations.